Transitions in electronic cigarette use among adults in the Population Assessment of Tobacco and Health (PATH) Study, Waves 1 and 2 (2013–2015). Issue 1 (25th April 2018) - Coleman, Blair; Rostron, Brian; Johnson, Sarah E; Persoskie, Alexander; Pearson, Jennifer; Stanton, Cassandra; Choi, Kelvin; Anic, Gabriella; Goniewicz, Maciej Lukasz; Cummings, Kenneth Michael; Kasza, Karin A; Silveira, Marushka L; et al.
Abstract : Introduction: This study assessed patterns of e-cigarette and cigarette use from Wave 1 to Wave 2 among adult e-cigarette users at Wave 1 of the Population Assessment of Tobacco and Health (PATH) Study. Methods: We examined changes in e-cigarette use frequency at Wave 2 among adult e-cigarette users at Wave 1 (unweighted n=2835). Adjusted prevalence ratios (aPR) were calculated using a predicted marginal probability approach to assess correlates of e-cigarette discontinuance and smoking abstinence at Wave 2. Results: Half (48.8%) of adult e-cigarette users at Wave 1 discontinued their use of e-cigarettes at Wave 2. Among dual users of e-cigarettes and cigarettes at Wave 1, 44.3% maintained dual use, 43.5% discontinued e-cigarette use and maintained cigarette smoking and 12.1% discontinued cigarette use at Wave 2, either by abstaining from cigarette smoking only (5.1%) or discontinuing both products (7.0%). Among dual users at Wave 1, daily e-cigarette users were more likely than non-daily users to report smoking abstinence at Wave 2 (aPR=1.40, 95% CI 1.02 to 1.91). Using a customisable device (rather than a non-customisable one) was not significantly related to smoking abstinence at Wave 2 (aPR=1.14, 95% CI 0.81 to 1.60). Conclusions: This study suggests that e-cigarette use patterns are highly variable over a 1-year period. This analysis provides the first nationally representative estimates of transitions among US adult e-cigarette users. Future research, including additional waves of the PATH Study, can provide further insight into long-term patterns of e-cigarette use critical to understanding the net population health impact of e-cigarettes in USA.